Manajemen Peran Guru Bimbingan dan Konseling dalam Pemberian Motivasi Terhadap Siswa yang Tidak Masuk Sekolah Melalui Layanan Home Visit di SMAN 1 Langkaplancar - Pajrin Nurlina; Sri Nurhilmi Fauziah; Atia Nurul Apriliani; Ratna Sa’adah (J-STAF: Siddiq, Tabligh, Amanah, Fathonah, 2024)
The purpose of this article is to examine the role of Guidance and Counseling (BK) teachers in providing motivation to students who often miss school. The problem of student absenteeism is a crucial issue in the world of education because it has a direct impact on academic achievement and students' social-emotional development. Counseling Guidance Teachers have a strategic role in identifying the causes of student absenteeism, providing guidance, and motivating students to return to school regularly. Through a qualitative approach method, this study collects data from in-depth interviews with BK teachers and students who have attendance problems. The results of the study show that a personal approach, in-depth counseling, and collaboration with parents and other schools are effective strategies implemented by Counseling Guidance Teachers. By understanding the background of the problems of students being treated through home visits, Counseling Guidance Teachers can provide appropriate interventions, help students overcome obstacles, and rebuild their motivation to learn. This study concludes that the role of Counseling Guidance Teachers is very significant in overcoming student problems, and the support and motivation provided by Counseling Guidance Teachers can increase the level of student attendance in school.